BIOCHEMICAL INFLUENCE OF FICUS EXASPERATA ON THE COLON OF HEALTHY WISTAR RATS AND ITS APOPTOTIC EFFECTS ON COLORECTAL CANCER - Olude, Olayemi Mujidat; Omoregie, Frank Osarumwense (FUDMA JOURNAL OF SCIENCES, 2025)
Dysregulation of the apoptotic pathway is one of the hallmarks of colorectal cancer progression. Apoptosis is a programmed cell death that occurs during normal development and aging. It is genetically regulated and involves intrinsic and extrinsic pathways. This study investigates how the methanol leaf extract of Ficus exasperata could promote apoptosis in colorectal cancer, and also the effect on colon antioxidant status of apparently healthy Wistar rats. This study was done in three phases. In the first phase, the acute toxicity check of the extract was done using a total of 12 rats. In phase 2, sub-chronic test was carried out with a total of 20 rats divided into four groups. 48 rats with 6 rats in each group were used in the third phase of this study. The third phase investigates the effect of the extract on some apoptotic genes. The oral toxicity test showed that the plant is not toxic to the animals as reflected in the antioxidant status and lipid peroxidation marker. This claim was further supported by the histology result. BAX, BCL2 and TP-53 were the apoptotic genes that were assayed for in this study. BCL-2 an antiapoptotic gene was found to be high in the group that took the carcinogen without treatment. The proapoptotic genes TP53 and BAX were significantly low in this group as well but the extract was able to mitigate the effect of the carcinogen hence, an increase in the relative gene expression of this proapoptotic gene in treated groups.